Analisis Motivasi, Kepuasan Kerja Dan Komitmen Organisasional Terhadap Kinerja Pegawai KPU - Hendri Afrianto (Universitas Islam Kadiri, 2020)
The research aim this to determine the effect of work motivation,job satisfaction and organizational commitment to the KPU Blitar Regency and KPU Blitar City. The research was conducted by questionnaire survey method to all employees. Data collection is done by distributing questionnaires to respondents. Questionnaires were distributed to employees of 20 respondents KPU Blitar Regency and 23 respondents KPU Blitar City.The analytical tool used is Multiple Linear Regression using SPSS application version 24. Result of research indicate that : (1) Work Motivation have a significant positive effect on Performance employees of KPU Blitar Regency and has no significant effect to Performance employees of KPU Blitar City; (2) Job Satisfaction has a significant positive effect on the Performance employees of KPU Kota Blitar and has no significant effect to Performance employees of KPU Blitar Regency; (3) Organizational Commitment has a significant positive impact on the Performance employees of KPU Blitar City and has no significant effect to Performance employees of KPU Blitar Regency; (4) Work Motivation, Job Satisfaction and Organizational Commitment together have a significant positive effect on the Performance employees of KPU Blitar Regency and KPU Blitar City. Job Satisfaction variable is the dominant variable in KPU Blitar City. Job Motivation variable is the dominant variable in KPU Blitar Regency.